From Environmental Clicktivism to Trash Cleanup : New Initiative of Instagram Account @Pandawaragroup - Erika, Desy; Alawi, Akhmad Roqi (Ultimacomm: Jurnal Ilmu Komunikasi, 2024)
Environmental awareness movements on social media are often limited to "clique activism". The possibility of participation or support from the community is only limited to the digital world without bringing change and action in real life. This research aims to find out how the communication process of the @pandawaragroup Instagram account can carry out cliktivism to real environmental activism. This research provides empirical arguments and evidence that activism on social media can produce real action. The @pandawaragroup account can prove that activism on social media is not just "cliktivism", but can lead to real participation, mobilisation and support. Activism on social media needs to pay attention to the principles in the process of environmental communication strategy, including social media activism is more likely to succeed in encouraging participation and real support when the message narrative is made simple, uses satirical language associated with real condition content, and starts with inspiring concrete examples and messages framed with hope and segmented in a special geographical environment that can encourage social and emotional closeness of the audience. Also, Pandawara Group succeeded in creating a personal branding as the iconic "Pandawa" group that motivates, inspires, and evokes emotions.